Transplantation of Neural Stem Cells Cotreated with Thyroid Hormone and GDNF Gene Induces Neuroprotection in Rats of Chronic Experimental Allergic Encephalomyelitis - Xiaoqing Gao; Guangqiang Hu; Li Deng; Guangbi Fan; Chaoxian Yang; Jie Du (Neural Plasticity)
The present study investigates whether transplantation of NSCs treated with T3 alone (T3/NSCs), or in conjunction with GDNF gene (GDNF-T3/NSCs), provides a better therapeutic effect than NSCs for chronic EAE. EAE rats were, respectively, injected with NSCs, T3/NSCs, GDNF-T3/NSCs, and saline at 10 days and sacrificed at 60 days after EAE immunization. The three cell grafted groups showed a significant reduction in clinical scores, inflammatory infiltration, and demyelination compared with the saline-injected group, and among the cell grafted groups, the reduction in GDNF-T3/NSCs group was the most notable, followed by T3/NSCs group. Grafted T3/NSCs and GDNF-T3/NSCs acquired more MAP2, GalC, and less GFAP in brain compared with grafted NSCs, and grafted GDNF-T3/NSCs acquired most MAP2 and least GalC among the cell grafted groups. Furthermore, T3/NSCs and GDNF-T3/NSCs grafting increased the expression of mRNA for PDGFαR, GalC, and MBP in lesion areas of brain compared with NSCs grafting, and the expression of mRNA for GalC and MBP in GDNF-T3/NSCs group was higher than that in T3/NSCs group. In conclusion, T3/NSCs grafting, especially GDNF-T3/NSCs grafting, provides a better neuroprotective effect for EAE than NSCs transplantation.